Cycle-dependent creep-fatigue deformation and life predictions in a nickel-based superalloy at elevated temperature. (15th September 2021) - Cheng, Lv-Yi; Wang, Run-Zi; Wang, Ji; Zhu, Shun-Peng; Zhao, Peng-Cheng; Miura, Hideo; Zhang, Xian-Cheng; Tu, Shan-Tung
Abstract: A series of strain-controlled creep-fatigue tests with various dwell times and strain ratios are carried out on a nickel-based superalloy at 650 °C. Aiming at the mechanical understanding of creep-fatigue behavior, a non-unified constitutive framework is used to describe macroscopic cyclic deformation process to understand creep-fatigue behavior. Afterward, the quantitative evaluation of creep-fatigue damage is quantitatively determined by the cycle-by-cycle strain energy density exhaustion (SEDE) approach. The effects of strain ratio and dwell time on creep-fatigue life endurances can be well revealed by the proposed life model, where all the data points are predicted within ± 1.5 error band. Particularly, life prediction capacities with long dwell times are further improved based on three-regime creep mechanism.